2013
DOI: 10.1007/s00595-013-0488-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between atmospheric pressure changes and abdominal aortic aneurysm rupture: results of a single-center study

Abstract: These findings suggest that atmospheric pressure and its changes do not affect the pathogenesis of AAA rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…After comparing these data with the weather conditions, no correlation between the AAARs and atmospheric pressure was detected, but a significant influence of the temperature changes was observed. The lack of a confirmed relationship between atmospheric pressure and aneurysm ruptures was also described by Molacek et al [22] in an analysis based on 54 ruptured aneurysm cases, and in a paper by Kurtoglou et al [23] based on 24 cases. Contradictory results were described in two other papers.…”
Section: Discussionmentioning
confidence: 54%
“…After comparing these data with the weather conditions, no correlation between the AAARs and atmospheric pressure was detected, but a significant influence of the temperature changes was observed. The lack of a confirmed relationship between atmospheric pressure and aneurysm ruptures was also described by Molacek et al [22] in an analysis based on 54 ruptured aneurysm cases, and in a paper by Kurtoglou et al [23] based on 24 cases. Contradictory results were described in two other papers.…”
Section: Discussionmentioning
confidence: 54%
“…Referring to controls, most published studies, to-date, do not specify their sources, 13,14 or use days of non-ruptured cases. [7][8][9]15,16 In our opinion, selecting controls from nonruptured days (or from non ruptured periods) only, instead of a random selection of controls from days in the study period (including ruptures and non-ruptured days) introduces potential for selection bias error. In this study, we tried to identify whether rAAA occur randomly throughout the year, which is why our controls were randomly selected throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 717 rAAA in a multicenter study. Most previously published studies analyze single-center data [7][8][9][13][14][15][16] or, at maximum, data from two different hospitals that include a lower number of cases, except three previous meta-analyses published in recent years. 8,18,19 Again, this reinforces the statistical power of our work, since we used a national database gathering information from all public hospitals in our region with admissions of rAAA (49 centers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence is also still inconclusive; some studies have found an association between low atmospheric pressure and the risk of AAA rupture, 2 , 4 6 whereas others have not. 1 , 7 Also, some studies suggest that while absolute atmospheric pressure itself may not serve as a risk factor, AAA rupture may in part be explained by day-to-day variation in air pressure. 1 , 3 We investigated these associations using approaches that, contrary to previous studies, account for nonlinearity, seasonality, and confounding by temperature.…”
Section: Introductionmentioning
confidence: 99%